Superfícies geomorfológicas do centro norte paranaense e evolução do relevo regional - Vargas, Karine Bueno (2017)
The spatial delimitation of this research encompasses an area of 2.930 km², located in the North Center of Paraná, an area comprised by the topographic map of Rio Bom, Mauá da Serra, Faxinal e Bairro dos França, in the scale of 1:50.000. The area lies in the transition of the Second to the Third Plateau of Paraná, in one of the edge plateaus of the Paraná Sedimentary Basin, named regionally as Cadeado Ridge. The main objective of this research was to analyze and characterize the genesis of the geomorphological surface of the studied area and to verify the implication of the crustal deformations on the evolution of the regional relief, considering the paleoclimatic and tectono-structural aspects that have influenced the modelling of the modern relief. The methodology applied crossed information obtained through geomorphological, geological and structural mapping with the elaboration of topographic and lithological profiles, morphometric analysis of the drainage and the relief from SRTM radar data, associated with in loco visits. On field were checked the geomorphological bedforms previously observed by aerial photos, which were characterized and described along with the geological formations that base the studied area and also the unconsolidated sedimentary deposits. As result of the research, five geomorphological surfaces were mapped, presenting stepped shape, with more than one lithology in their domains, characterizing themselves as structural surfaces, whose genesis is associated to local structures, as the Mauá da Serra Structural Hight, which has the feature of a dome, is partially eroded and is associated with a laccolite of large span. Each one of these geomorphological surfaces presents Cenozoic deposits with different characteristics, on their structural and textural aspects, that denote variations of the generative environment. The isolation of the Mauá da Serra Structural High in relation to the cuestiform relieves of the Serra Geral, north and south, occurred from the control of the level base exerted by the Ivaí e Tibagi rivers, because the tectonic continued to happen, after the arching, but with less intensity. That fact resulted in balanced erosions and uplifts, which were not enough to destroy the structural high or to project it to higher altitudes.